Analisis Teologis-Kritis terhadap Teori Anonymous Christians Karl Rahner dan Implementasinya bagi Gereja Masa Kini - Barnabas; Busno; Marlies Dorien Grevers; Randa Kisara (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2026)
This article focuses on highlighting the theory of Anonymous Christians developed by Karl Rahner. This theory states that a person can attain salvation even if they do not explicitly identify themselves as a Christian. This concept emphasizes that God's grace works universally and transcends the boundaries of formal religion. Rahner combines Catholic Thomistic thought with existentialist philosophy to emphasize that humans have an inherent openness to God. The strengths and weaknesses of this theory present an interesting area for research. This study uses critical analysis methods to explore the relevance of this theory in relation to religious pluralism, secularization, and the challenges of globalization. The research findings indicate that the theory of Anonymous Christians remains relevant in fostering interfaith dialogue and social harmony in the modern era. This article emphasizes that the Church can use this concept as a basis for a more dialogic evangelization mission, strengthening interreligious tolerance, and responding to the dynamics of religious life in the digital era. This theory, in itself, shifts the understanding of salvation from an exclusive understanding to a more inclusive concept of salvation, and has received criticism from groups that view salvation exclusively.